Marxism, Existentialism, and Law - Trazegnies Granda, Fernando de (1968)
The author starts from the approach of the legal philosopher Nicos Poulantzas, who proposes to reconcile the philosophy of law with an existential-Marxist vision. Thus, Poulantzas analyzes the importance of phenomenology and from it seeks to discover the relationship between fact and value, finding in existentialism the essential requirements to counteract the problems brought about by phenomenology and, in this way, reconcile fact and value.  From this premise, value and fact are conceived as two moments of the human act that must be understood in a normative sociological context. At another point, Poulantzas will also address the link between freedom and necessity, as well as the function of law within society. Finally, for the author, Poulantzas does a meritorious work that seeks to analyze law from a perspective devoid of the juridical positivism that many jurists currently profess.